AMERICAN CAESAR: Douglas MacArthur, 1880-1964 - Muller, V.C. (Scientia Militaria - South African Journal of Military Studies, 2011)
The narrative begins on a hilltop in Tennessee in 1863. It is Missionary Ridge where 18-year-old Lt Arthur MacArthur, the father of Douglas MacArthur, won the Medal of Honour. Arthur, who later became a Lieutenant General, was the driving spirit behind Douglas throughout his career.